Deafness and Its Burdens - Prevention and Control - Aremu, Dr. Shuaib Kayode (International Journal of Innovative Research in Medical Science, 2019)
There is high burden of deafness globally is largely preventable and may be avoidable. Over 5% of the population of the world (466 million people) are living with disabling hearing loss (432 million adults and 34 million children). In 2002 WHO noticed that hearing loss has become a burden globally and major attentions were being paid on children and youth with adult being neglected. Hearing loss is the second most common cause of years lived with disability .Hearing impairment occurs when there is reduction in hearing acuity. Hearing impairment is a neglected chronic otological disorder with varying aetiology. Permanent childhood hearing loss is a significant health condition and its detection through screening with oto-acoustic emissions and/or auditory brainstem response is feasible and made early intervention possible and rewarding. Nationwide disability surveys estimated that hearing loss is the second most common cause of disability. This has posed a greater challenge to the practice of otolaryngology worldwide. A lack of skilled manpower, human resources and diagnostic facilities make this problem a huge challenge.